2018
DOI: 10.3390/fluids3040095
|View full text |Cite
|
Sign up to set email alerts
|

Acoustics of Bubble Arrays: Role Played by the Dipole Response of Bubbles

Abstract: A model for acoustic transmission through a 2D square crystal of R-radius bubbles with a lattice constant L was previously proposed. Assuming a purely monopole response of the bubbles, this model offers a simple analytical expression of the transmission. However, it is not applicable when the bubbles are too close to each other ( L / R < 5). This article proposes an extension of the model by including the dipole response of the bubbles. Comparisons with numerical and experimental results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…To meet the requirements of portable biomedical devices, the bubble removal method can be implemented by other means, e.g., forced fluid flow of the electrolyte or on-chip reversal of the electrolysis 39 . Future work should explore multilevel amplitude or phase control of sound waves exploiting the resonant behavior of the microbubbles at specifically controlled sizes 40 43 . Spatial ultrasound modulators extend the capabilities of ultrasound applications and will be essential for medical imaging 13 , 44 , nondestructive testing 15 , holographic acoustic tweezers 8 , 25 , transcranial ultrasonic focusing 12 , acoustic fabrication 9 and cell assembly 10 .…”
Section: Discussionmentioning
confidence: 99%
“…To meet the requirements of portable biomedical devices, the bubble removal method can be implemented by other means, e.g., forced fluid flow of the electrolyte or on-chip reversal of the electrolysis 39 . Future work should explore multilevel amplitude or phase control of sound waves exploiting the resonant behavior of the microbubbles at specifically controlled sizes 40 43 . Spatial ultrasound modulators extend the capabilities of ultrasound applications and will be essential for medical imaging 13 , 44 , nondestructive testing 15 , holographic acoustic tweezers 8 , 25 , transcranial ultrasonic focusing 12 , acoustic fabrication 9 and cell assembly 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Another question is how to generalize our theory to elastic solid media containing bubbles. As the authors have demonstrated in [8][9][10][11], for elastic media with very low shear stress, the primary mechanism of the first band gap is still caused by the resonance of the bubble. Therefore, we believe that our theory can be generalized and applied to such a system without much difficulty.…”
Section: Absorption Effect and The Possibility Of Generalizationmentioning
confidence: 94%
“…In earlier works [6,7,42,43], it was shown that, in a hybrid structure, comprising a decorated membrane set on a closed cavity of depth d, the required impedance of the membrane that can lead to zero reflection (and total absorption) is given by…”
Section: Hybrid-membrane Resonator With the Partial Asbcmentioning
confidence: 99%